High waist-to-hip ratio levels are associated with insulin resistance markers in normal-weight women - Benites Zapata, Vicente A. (2018)
Aim: To assess the association between high waist-to-hip ratio (WHR) levels and insulin resistance (IR) or hyperinsulinemia after oral glucose tolerance test (OGTT) in a sample of normal-weight women. Methods: We conducted an analytical cross-sectional study in euthyroid non-diabetic women, who attended the outpatient service of a private clinic in Lima-Peru from 2012 to 2016. Participants were divided in two groups according to the presence or absence of high WHR levels, IR or hyperinsulinemia after OGTT. We considered WHR values > 0.85 as high levels. IR was defined as a Homeostasis Model Assessment (HOMA-IR) value > 2.39 and hyperinsulinemia after OGTT as a serum insulin value ≥ 80μU/mL after 120 min of 75-g glucose intake. We elaborated crude and adjusted Poisson generalized linear models to evaluate the association between high WHR levels and IR or hyperinsulinemia after OGTT and reported the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI).